Effects of Estradiol and Progesterone-Induced Intracellular Calcium Fluxes on Toxoplasma gondii Gliding, Microneme Secretion, and Egress - Zhang, Xiao; Zhang, Heng; Fu, Yong; Liu, Jing; Liu, Qun (Frontiers in Microbiology, 2018)
Research has shown that estrogen is present and plays a critical role in vertebrate reproduction and metabolism, but the influence of steroids on Toxoplasma gondii has received less attention. Our data showed that estradiol and progesterone induced parasitic cytosolic Ca2+ fluxes. This process required estrogen to enter the cytoplasm of T. gondii, and cGMP-dependent protein kinase G (PKG) and phosphoinositide-phospholipase C (PI-PLC) emerged as important factors controlling parasitic intracellular Ca2+ signals. Cytosolic Ca2+, which is regulated by estradiol, was mostly mobilized from acidic organelles. Moreover, cytosolic Ca2+ slightly increased MIC2 protein secretion and promoted the gliding motility and egress of parasites, thus enhancing the pathogenicity of T. gondii, as shown in our previous research. We subsequently determined that the main source of Ca2+ regulated by progesterone was a neutral store. In contrast to the findings of estradiol, progesterone reduced MIC2 protein secretion and inhibited the gliding motility of parasites, which may decrease their pathogenicity. Additionally, unlike in mammals, estradiol and progesterone had no effect on nitric oxide (NO) or reactive oxygen species (ROS) production in T. gondii.